Gestures and words before 2 years: effect of age and gender - García Fernández, Inaki; Ezeizabarrena Segurola, María José; Murciano, Aroa (Revista de Investigación en Logopedia, 2021)
Data of gestures and of receptive and expressive vocabulary of 754 children (8- to 24-month-old) obtained with CDI-1v, the Basque adaptation of the parental questionnaire CDI-1, confirmed the close relationship between the early verbal and non-verbal language inventories. In addition to the age effects found in all the CDI-1 scales, some gender differences in Gestures and actions, as well as in receptive vocabulary resulted in favour of girls, in line with studies of other languages conducted with 8- to 18-month olds using the same methodology. Data obtained using the CDI-1v with a more extended age range (8 to 24 months) revealed that gender differences vary in strength not only across scales (e.g. higher effect in the total of Gestures than in vocabulary) but in directionality (higher scores for boys in some types of Gesture and actions, and higher scores for girls in others).